2010
DOI: 10.1103/physrevb.82.165126
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature thermoelectric response of double-dopedSrTiO3epitaxial films

Abstract: SrTiO3 is a promising n-type oxide semiconductor for thermoelectric energy conversion. Epitaxial thin films of SrTiO3 doped with both La and oxygen vacancies have been synthesized by pulsed laser deposition (PLD). The thermoelectric and galvanomagnetic properties of these films have been characterized at temperatures ranging from 300 K to 900 K and are typical of a doped semiconductor. Thermopower values of double-doped films are comparable to previous studies of La doped single crystals at similar carrier con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 28 publications
(28 reference statements)
4
49
1
Order By: Relevance
“…After the discovery of large thermoelectric power factor in La doped STO, 20 several thin film oriented investigations were performed on doped STO using pulsed laser deposition method. As doped STO remains the best n-type oxide thermoelectric material, several in-depth investigations studied the effect of single dopant, 100 multiple dopants, 101,114,115 and their Ruddlesden-Popper phases 116 on the thermoelectric properties of STO based thin films. Interestingly, the very first exploration of thermoelectric properties of heavily Nb doped ternary phase diagram of CaTiO 3 -SrTiO 3 -BaTiO 3 was carried out using pulsed laser deposition.…”
Section: A Titanatesmentioning
confidence: 99%
See 3 more Smart Citations
“…After the discovery of large thermoelectric power factor in La doped STO, 20 several thin film oriented investigations were performed on doped STO using pulsed laser deposition method. As doped STO remains the best n-type oxide thermoelectric material, several in-depth investigations studied the effect of single dopant, 100 multiple dopants, 101,114,115 and their Ruddlesden-Popper phases 116 on the thermoelectric properties of STO based thin films. Interestingly, the very first exploration of thermoelectric properties of heavily Nb doped ternary phase diagram of CaTiO 3 -SrTiO 3 -BaTiO 3 was carried out using pulsed laser deposition.…”
Section: A Titanatesmentioning
confidence: 99%
“…123 Despite this advantage, the titanates are prone to be highly nonstoichiometric 124 with profound effect on this physical properties, 121,125 especially thermoelectric properties. 101,126 For example, in the case of STO, due to the presence of deep valence bands with respect to the vacuum level, only n-type doping is thermodynamically feasible. 127 Trivalent ions such as La, Pr on the A-site (Sr), pentavalent ions such as Nb on the B-site (Ti), oxygen vacancies, or a combination of these were used as common dopants to achieve n-type conduction in STO.…”
Section: A Titanatesmentioning
confidence: 99%
See 2 more Smart Citations
“…SrTiO 3 is one of the most important candidate n-type thermoelectric oxides, 1,2 and many researchers have studied the thermoelectric properties of SrTiO 3 -based materials. [3][4][5][6][7] There have been many investigations into fabrication methods for SrTiO 3 ceramics, for example, the hydrothermal method, 8 the sol-gel method, 9 combustion synthesis combined with spark plasma sintering (SPS), 10 and the solid-state reaction method (SSR). 11 In our previous studies, it was found that performing the solid-state reaction method in an oxygen-reduced atmosphere (reduced SSR method) could significantly improve the thermoelectric performance of SrTiO 3 -based materials.…”
Section: Introductionmentioning
confidence: 99%